Asertividad comunicacional para un aprendizaje significativo en línea en la Unidad Educativa Siete de Octubre del cantón Quevedo, año 2020 - Geronimo Herbacio, Diana (2021)
This investigative work focuses its attention on the communicational assertiveness that exists between the student-teacher relationship, of the students in the Siete De Octubre Educational Unit, showing that, during the change from face-to-face to virtual modality, it directly affected the communicative relationship that existed Before the pandemic, the objective was to determine strategies that help promote good communication in the learning environment, it is precisely on this that the project bases its importance, seeking to reach practical solutions. The research modality has been of a mixed nature, that is, qualitative and quantitative, quantitative because surveys were used through essentially and clearly quantifiable methods, to obtain results that later served to reach conclusions, and qualitative because texts, documents that served to nurture the research, in addition to its use to be able to interpret the results of the surveys and capture their reality through concepts and words understandable to the critical eye of the reader.